COVID-19 Crisis: Challenges of Online Learning in One University in Lesotho - Makafane, David Teboli; Chere-Masopha, Julia (African Perspectives of Research in Teaching & Learning, 2021)
In 2020, COVID-19 crisis forced learning organisations, Lesotho universities included, to suspend their face-to-face teaching and migrate their learning activities online. This was a new way of learning to many students. The study reported in this paper investigated the challenges students in one Lesotho university were experiencing with online learning. Specifically, the study focused on the types of challenges the students were experiencing, (2) how the students dealt with these challenges and (3) the general implications. The study employed a qualitative approach in which telephone semi-structured interviews were used to collect data from 12 undergraduate students in the Faculty of Education. The findings of this study suggest that the challenges that were experienced by the students were mainly influenced by their personal attributes, pedagogical issues and how the university supported them. The study concludes that the conditions under which online learning was offered in this university were not conducive to enhance effective student participation online; the students were not receiving quality learning; and others were even excluded from learning by the existing digital conditions. The study recommends that the University should invest more in the digital infrastructure, processes and techniques that would enhance students’ experiences with online learning. The University should also find ways of assisting students with access to digital devices and making internet easily accessible to these students.
Article published in the African Perspectives of Research in Teaching & Learning (APORTAL) Vol 5(1): (2021)
Keywords: COVID-19; Learning access; Learning experiences; Learning Management system; Learning platform; Online learning challenges; Online teaching and learning.; Covid-19 (Disease); Web-based instruction; Educational acceleration; Mediated learning experience